2021
DOI: 10.3389/fmicb.2021.645331
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Variability Associated With CRISPR-Mediated Gene Replacements at the Phytophthora sojae Avr1b-1 Locus

Abstract: Transcriptional plasticity enables oomycetes to rapidly adapt to environmental challenges including emerging host resistance. For example, the soybean pathogen Phytophthora sojae can overcome resistance conferred by the host resistance gene Rps1b through natural silencing of its corresponding effector gene, Avr1b-1. With the Phytophthora CRISPR/Cas9 genome editing system, it is possible to generate site-specific knock-out (KO) and knock-in (KI) mutants and to investigate the biological functions of target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To perform biomass measurement, total gDNA was extracted using a hexadecyltrimethylammonium bromide method (May & Ristaino, 2004) and quantified by 1% agarose gel electrophoresis. Quantitative PCR of gDNA was performed using CFX Connect (BioRad) as described by Gu et al (2021) to obtain biomass measurements. Genomic DNA abundance or relative gene expression was measured by a 2 −ΔΔCt method using the Actin genes from both P. infestans and N. benthamiana as endogenous controls.…”
Section: Methodsmentioning
confidence: 99%
“…To perform biomass measurement, total gDNA was extracted using a hexadecyltrimethylammonium bromide method (May & Ristaino, 2004) and quantified by 1% agarose gel electrophoresis. Quantitative PCR of gDNA was performed using CFX Connect (BioRad) as described by Gu et al (2021) to obtain biomass measurements. Genomic DNA abundance or relative gene expression was measured by a 2 −ΔΔCt method using the Actin genes from both P. infestans and N. benthamiana as endogenous controls.…”
Section: Methodsmentioning
confidence: 99%
“…For double knockout mutants, we began with the single knock out mutants. After culturing the single knock out mutants for at least three generations in antibiotic-free plates for more than 2 weeks, the mutants could no longer grow on G418 antibiotic plates 45 , 46 . Using a single knock out mutant of PsTET1 that had lost the resistance to G418 (KOT1-9), we conducted another CRISPR-mediated gene replacement to knock out the other gene PsTET3 as described 45 , 46 .…”
Section: Methodsmentioning
confidence: 99%
“…This indicates the presence of a genetic mechanism, gene silencing due to the destruction of transcription elements, by which avirulence is lost. The naturally occurring Avr1b -silenced also suggests that Avr1b is not an essential effectors, and the gene knockout assay also demonstrated that PsAvr1b is not required for full virulence of P. sojae ( Gu et al, 2021 ).…”
Section: Destruction Of Transcription Elementsmentioning
confidence: 99%